Reaktualisasi Pendidikan Karakter di Era Disrupsi - Sayyidi Sayyidi; Muhammad Abdul Halim Sidiq (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat - Islamic Institute of Syarifuddin Lumajang, Indonesia., 2020)
The development of education always changes with the times, the wider the access to interaction the wider the challenges. Students who have been educated in the past face real challenges today, while children who are currently educated will face challenges in the future. The transformation of education has indeed become an inevitable necessity to keep up with the flow of disruption. Education in the past was quite easy to make children become obedient and easily regulated individuals even though the function of three education center was imbalanced and mostly played a role in the school environment. However, the results are satisfying in shaping the character and personality of a good child. It is different from the current conditions in which the role of the family and community education environment must begin to be played maximally. This condition is the impact of the era of disruption that can not be dammed, not only the mindset of students who are contaminated by the thought of